Fluoridation and Social Equity - Brian A. Burt, BDS, MPH, PhD (Blackwell Synergy, 2002)
The overall reduction in caries prevalence and severity in the United States over recent decades is largely due to widespread exposure to fluoride, most notably from the fluoridation of drinking waters. Despite this overall reduction, however, caries distribution today remains skewed, with the poor and deprived carrying a disproportionate share of the disease burden